Cognitive behavioural therapy for aggression among individuals with moderate to severe acquired brain injury: a systematic review and meta-analysis. (15th October 2018) - Iruthayarajah, Jerome; Alibrahim, Fatimah; Mehta, Swati; Janzen, Shannon; McIntyre, Amanda; Teasell, Robert
ABSTRACT: Background : Aggression is common after an acquired brain injury (ABI). Cognitive behavioural therapy (CBT) is a form of psychotherapy, in which therapists help patients to identify their maladaptive behaviours. Objective : The objective of this systematic review and meta-analysis was to evaluate the effectiveness of CBT interventions in treating aggression in an ABI population. Methods : A systematic literature search was conducted using: PubMed/MEDLINE, CINAHL, EMBASE and PsycINFO from database inception to August 2016. English articles were included if: at least 50% of the study sample had a moderate to severe ABI, there were at least three adult human participants, and use of a CBT intervention for the treatment of aggression. Results : Seven articles met inclusion criteria: one RCT, an RCT crossover and five pre-post trials. Of these, four articles were included in a pre-post meta-analysis for treatment efficacy on subscales of the State Trait Anger Expression Inventory (STAXI) and STAXI-2 outcome measures. The meta-analysis found CBT was effective in moderating the external behaviours of aggression, but not internal anger. Conclusion : The differences in outcomes may be related to the differential management of anger expression and anger suppression. CBT shows promise, but further studies with comparator groups are needed before conclusions about its efficacy can be made.